Association of Severity of Diabetic Retinopathy with Levels of HbA1c - Raja Muhammad Taimoor Khan, Haroon Saleem, Shahid Anwar Bhatti, Muhammad Usman Sadiq, Muhammad Irfan Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the association between the severity of retinopathy and HbA1c status in patients with diabetes mellitus. Study design: A Cross-sectional study. Place and duration: In the department of Ophthalmology, Al Shifa Trust Eye Hospital, Rawalpindi for six-months duration from December 2020 to May 2021. Methods: The study included 120 patients of both sexes with type I and type II diabetes, aged 35-80 years. Full ophthalmology examination was carried out including the slit lamp examination, best visual acuity correction, fundus examination and Goldman applanation tonometry. The diabetic retinopathy is graded from Grade 0-Grade V. Results: Of the 120 cases, 58 (49%) were male and 52 (51%) were female. 60 ± 2.4 years was the mean age of patients with 35-80 years of age range for men and 40-75 years for women. Figure 1 is a bar graph showing the severity of diabetic retinopathy. Grade-I diabetic retinopathy was seen in 45(37.5%) patients and Grade-V was noted in 5%. The good control of glycemia was seen in 38 patients and 20.8% had Grade III glycemic control. The worst glycemic control was seen in patients with Grade-IV diabetic retinopathy having 11.8 of HbA1c. Conclusions: This analysis found that severe diabetic retinopathy was seen in patients with poor control of glycemia in comparison to patients with better diabetes control. There is a direct relationship between the severity of diabetic retinopathy and levels of HbA1c levels. Keywords: Diabetic retinopathy, Vitreous hemorrhage, HbA1C, Proliferative diabetic retinopathy, Non-proliferative diabetic retinopathy.